الكريستولوجيا (طبيعة السيد المسيح) في فلسفة جون هيك - Muhammed, Anmar Ahmad (FSM Vakıf Üniversitesi)
تتحدث هذه المقالة عن حقيقة طبيعة السيد المسيح بين ألوهيته وبشريته أو ما تسمى حسب المصطلح المسيحي ب )الكرستولوجيا( وتتناول حقيقة شخصية المسيح وأعماله ودعوته وكل ذلك من منظور فلسفة وأفكار إحدى أهم الشخصيات العلمية والأكاديمية والفلسفية واللاهوتية في الديانة المسيحية في عصرنا الحالي وهو البرفسور البريطاني 1922 م(، إذ تقدم لمحات وتصورات عن طبيعة شخصية المسيح الحقيقية )كما يراها الفيلسوف - جون هيك ) 2012 هيك(، والتي بالتأكيد تخالف العقيدة والتقليد المسيحي الممتد لمئات السنين، تلك العقيدة التي أقرت في مجمعي نيقيّة وخلقيدونيّة المسكونيين، والتي تذهب إلى وجود طبيعتين داخل السيد المسيح هما الطبيعة الإلهية والطبيعة البشرية اجتمعتا وامتزجتا معا وكونتا الإله المتجسد.

Bu makale, mesihi terimine binaen isimlendirilen Kristolojiye, İsa Mesih’in ulûhiyeti ve beşeriyeti arasında kalan doğasına değinmektedir. Aynı zamanda İsa Mesih’in çağrısını, yaptıklarını, kişiliğini vb. konuları felsefenin ve günümüz Hristiyanlığındaki ilahiyat, felsefi, akademik ve ilmi alanda en önemli şahsiyetlerden biri olan John Hick’in görüşlerinin perspektifinden ele almaktadır. Öyle ki filozof Hick’in öngördüğü gibi İsa Mesih’in kişilik doğasına, Kalkedon ve Birinci İznik Konsili’nde kararlaştırılmış olan Hıristyanlığın akidesinin ve geleneğinin yüz yıllar boyu ters düşmesine, İsa Mesih’in bir araya gelen, birbirine karışan, bir bedende vücut bulmuş ilahı meydana getiren tanrısal ve beşeri iki doğasının olduğuna dair önbilgiler vermektedir.

This article discusses the true nature of Jesus Christ between his divinity and his humanity, or it so-called in the Christian term (Christology), It contains the reality of Christ’s personality, his work and his call, all of that from the perspective of the philosophy and ideas of one of the most important scientific, academic, philosophical and theological figures in the contemporary Christian religion, The British professor John Hick (1922- 2012), It provide us insights into the nature of Christ’s true personality (as the philosopher Hick sees) which certainly contradicts the doctrine as well as the Christian tradition which extended for hundreds of years, that doctrine endorsed by the Ecumenical Councils of Nicaea and Chalcedon which believe in existence of two natures within Christ is the divine nature and the human nature that have met and merged together and become the incarnate God.
John Hick Felsefesine Göre Hristoloji (Mesih’in Doğası)
Christology (The Nature of Jesus Christ) According to the Philosophy of John Hick
Keywords: طبيعة السيد المسيح; الكرستولوجيا، التجسد; جون هيك، السيد المسيح; John Hick; İsa Mesih; Kristoloji; Tecessüd; İsa Mesih’in doğası; Christ; Christology; Incarnation; Nature of Christ